Spiritual care in Australian general practice nursing: An interpretive descriptive study. (14th June 2022) - Schreiber, Christine; Verrall, Claire; Whitehead, Dean
Abstract: Spiritual care as an aspect of holistic or person‐centered care has been well documented. Studies on spirituality and spiritual care in nursing have taken place in various countries and contexts. Studies about spiritual care from the nurse perspective in the primary healthcare setting of Australian General Practice are not evident. Using an interpretive description study design, data about views on spirituality, spiritual care experiences, and descriptions about any spiritual care provided were collected from eight practice nurses. Four themes were drawn from the findings: the personal importance of spirituality and spiritual care to nurses and patients, spiritual care as an aspect of person‐centered care, spiritual care practices, and barriers and enablers to addressing spiritual needs. Participants identified that practice nurses require improved education about spirituality to adequately address spiritual needs as expressed by patients, as well as the tools to be able to provide spiritual care. They also identified that documentation templates used in general practice should include prompts to address spiritual and/or religious needs.